Beam shaping with higher laguerre-Gaussian orders for high power bessel beams - Siems, Malte Per; Thomas, Jens Ulrich; Vetter, Christian; Bergner, Klaus; Gross, Herbert; Nolte, Stefan (2019 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2019, 2019)
Ultra short pulse lasers offer unique possibilities in material processing applications. The extremely high intensities in the focus of a femtosecond or picosecond laser pulse cause non-linear absorption inside an otherwise transparent material. This leads to a highly localized deposition of energy and can be used to create tailored modifications inside the bulk of the material without damaging the surface [1]. The induced structures can for example be arranged as a breaking layer for cleaving glass. Tailored beam-shaping techniques can significantly improve this process. Using Bessel-Gaussian focal lines create long and thin modifications which dramatically improve the breaking process and quality of the resulting edge surface [2]. To create the Bessel-Gaussian beams an axicon, as shown in Fig. 1, is typically used in high power applications due to its high damage threshold.
CRIS-Team Scopus Importer:2023-04-20